Model Partisipatif Focus Group Discussion untuk Sejarah Lokal dan Dakwah Kultural di Tuban - Siti Kris Fitriana Wahyu Lestari; Abdul Rahmat Albustomi; Supriyanto; Auliya Urokhim (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2026)
The marginalization of local history and the weakening relationship between younger generations and indigenous Islamic heritage pose significant challenges for coastal communities in Indonesia. This study examines a community empowerment model employing Focus Group Discussion (FGD) as a participatory method to reconstruct inclusive local historiography while revitalizing culturally based Islamic preaching (dakwah kultural) in Tuban Regency, East Java. Grounded in a Participatory Action Research approach, the intervention involved 60 purposively selected participants, including academics, university students, religious leaders, local history communities such as Tuban Bercerita, and members of the wider community. The FGD was organized into three thematic sessions focusing on local history reconstruction, dakwah kultural, and multi-stakeholder collaboration. Thematic analysis revealed a strong public demand for accessible historical narratives, widespread recognition of inaccuracies in official historiography, and the emergence of culturally grounded preaching models integrating local symbols, such as the keris, as media for conveying Islamic values. The process also generated tangible academic and practical outcomes, including the establishment of collaborative networks between universities and grassroots communities. These findings demonstrate that FGD functions not only as a dialogical platform for knowledge co-production but also as a mechanism for strengthening social capital, fostering collective awareness, and facilitating the intergenerational transmission of local identity. This study offers a replicable bottom-up framework for integrating cultural heritage into Islamic preaching and community empowerment initiatives.